The Effect of Cucumber Juice on the Elderly Hypertension in Citalahab Village, Pandeglang District in 2020 - Winata, Nova Pandu; Indrayani, Triana; Carolin, Bunga Tiara (Journal of Global Research in Public Health, 2020)
Hypertension is a risk factor of the occurrence of cardiovascular and kidney disease. Male and female have the same risk of hypertension. Intake with food material modification containing potassium and magnesium becomes one of complementary therapy to decrease blood pressure, one of them is cucumber. Cucumber is vegetable grows in all seasons and easily obtained in Indonesia. It also has potassium and magnesium content. This research used quasi-experimental research through two group pretest and posttest design approach. The research population was 100 elderly with hypertension in which there were 34 respondents who became the research samples. The sampling technique in this research was purposive sampling technique. Research result on the distribution of frequency on control group was that most of them were at the age of ≤ 65 years old (82.4%) and were mostly female (76.5%). Meanwhile, in the intervention groups, most of them were at the age of ≤ 65 years old (88.2%) and were mostly females as well (88.2%). It obtained result that there was different blood pressure on the hypertension sufferer in before and after the consumption of cucumber juice on intervention group. Wilcoxon Signed-Rank test showed p value < 0.05 which means that there was effect of cucumber juice on Elderly hypertension between the control and intervention groups